2015
DOI: 10.1159/000442306
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genetic Variants of PPARγ and PPARα Encoding Peroxisome Proliferator-Activated Receptors and Susceptibility to Ischemic Stroke in Chinese Han Population

Abstract: Background: PPARγ and PPARα belong to a receptor family of ligand-activated transcription factors involved in the regulation of inflammation, cellular glucose uptake, protection against atherosclerosis and endothelial cell function. Through these effects, they might be involved with the ischemic stroke (IS). Methods: One thousand two hundred ninety-six subjects from the Chinese Han Population were chosen to assess the nature of the functional polymorphisms of PPARs and any links with IS. Multivariate logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…CYP2C19 gene polymorphisms are associated with long-term recurrent risk of ischemic stroke [45]. Peroxisome proliferator-activated receptors could be a protective factor for ischemic stroke in the Chinese Han population [46]. A previous study showed that genetic factors are associated with age at stroke onset and sex [47].…”
Section: Discussionmentioning
confidence: 99%
“…CYP2C19 gene polymorphisms are associated with long-term recurrent risk of ischemic stroke [45]. Peroxisome proliferator-activated receptors could be a protective factor for ischemic stroke in the Chinese Han population [46]. A previous study showed that genetic factors are associated with age at stroke onset and sex [47].…”
Section: Discussionmentioning
confidence: 99%
“…Tong et al. (2016) additionally reported a protective effect against IS formation in a Chinese population. In contrast, another study by Wang et al.…”
Section: Discussionmentioning
confidence: 96%
“…Li et al, 2016;Z. J. Liu et al, 2010;Lu et al, 2009;Shen & Ha, 2005;Sun, 2010;Tong et al, 2015Tong et al, , 2016Wang et al, 2019;Wei et al, 2013;Yuan, 2008;Zafarmand et al, 2008). Of these, 10 case-control studies focused on rs1801282 C/G polymorphism (Bazina et al, 2015;L.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The 162Leu/Val genotype is more frequent in the German, Danish, Czech, and Brazilian population, whereas the 162Val/Val is more frequent only in the Tunisian population [47]. It is possible to demonstrate a much stronger association between this polymorphism (V162 allele), than the intron 7 G/C polymorphisms with stage C heart failure.…”
Section: Single Nucleotides Polymorphisms (Snps)mentioning
confidence: 99%